2020
DOI: 10.1101/2020.03.12.989830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Purging of deleterious mutations during domestication in the predominant selfing crop soybean

Abstract: As a predominant plant protein and oil source for both food and feed, soybean is unique in that both domesticated and wild types are predominantly selfing. Here we present a genome-wide variation map of 781 soybean accessions that include 418 domesticated (Glycine max) and 345 wild (Glycine soja) accessions and 18 of their natural hybrids. We identified 10.5 million single nucleotide polymorphisms and 5.7 million small indels that contribute to within-and between-population variations. We describe improved det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 88 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Direct comparison between corresponding chromosome sequences of the Hwangkeum and Williams 82 assemblies identified 1,788,320 SNPs and 517,907 indels (< 50 bp) (Table S6 and File S2). Interestingly, the number of SNPs is similar to the combined number (1,678,164) of heterozygous (4,919), missing (713,953), and homozygous non-reference (959,292) SNPs for Hwangkeum in the 30,753,511 SNP set without the minor allele frequency filter detected in the 781 soybean haplotype map set (Kim et al 2021). The number of indels is also similar to the combined number (470,389) of heterozygous (28,639), missing (303,784), and homozygous non-reference (137,966) indels for Hwangkeum in the 5,717,052 indel set without the minor allele frequency filtration detected from the same set.…”
Section: Genome Structure Comparison With Other Publicly Available Soybean Genomesmentioning
confidence: 69%
See 1 more Smart Citation
“…Direct comparison between corresponding chromosome sequences of the Hwangkeum and Williams 82 assemblies identified 1,788,320 SNPs and 517,907 indels (< 50 bp) (Table S6 and File S2). Interestingly, the number of SNPs is similar to the combined number (1,678,164) of heterozygous (4,919), missing (713,953), and homozygous non-reference (959,292) SNPs for Hwangkeum in the 30,753,511 SNP set without the minor allele frequency filter detected in the 781 soybean haplotype map set (Kim et al 2021). The number of indels is also similar to the combined number (470,389) of heterozygous (28,639), missing (303,784), and homozygous non-reference (137,966) indels for Hwangkeum in the 5,717,052 indel set without the minor allele frequency filtration detected from the same set.…”
Section: Genome Structure Comparison With Other Publicly Available Soybean Genomesmentioning
confidence: 69%
“…After three weeks' growth, a bulk of young trifoliolate leaf tissues was collected for genomic DNA extraction. Note that the seeds of Hwangkeum used in this study came from the line of Hwangkeum that had been subject to single plant selection at least twice during our recent 180K SoyaSNP array and genome resequencing studies (Lee et al 2015;Kim et al 2021). Genomic DNAs for the generation of Illumina short-read (Illumina, San Diego, CA, USA) and PacBio SMRT long-read sequences (Pacific Biosciences, Menlo Park, CA, USA) were extracted using the CTAB method, as described by Saghai-Maroof et al (1984).…”
Section: Plant Materials and Sequencingmentioning
confidence: 99%
“…2018), we didn’t find clear evidence of accumulation of deleterious load in the crop pool. Interestingly, a recent study in soybean found a genome wide reduction of the deleterious alleles in domesticated soybean relative to wild soybean (Kim et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with a previous work on sorghum (Smith et al, 2019), and evidence in other plant and animal domesticates (Liu et al, 2017; Moyers et al, 2018), we didn’t find clear evidence of accumulation of deleterious load in the domesticated pool. Interestingly, a recent study in soybean found a genome wide reduction of the deleterious alleles in domesticated soybean relative to wild soybean (Kim et al, 2020). These authors suggested that the increase of self crossing associated with domestication may have helped purging the deleterious load, partly by exposing to selection deleterious variants in homozygous state, a process suggested also in cassava (Ramu et al, 2017) and grape (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation